(3GdeONd dJMbjb GdQjGOI GdhXjajI ddYGedjf GdLOO hGdbOGejs - (3eMeO eMeO(B, (3GHQGgjes ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2008)
(3JMOjO hENJjGQ GdeSGQGJ GdhXjajI hJScjf GdYGedjf aj GdeSGQGJ GdedGFeI(B- (3fbWI GdHOGjI GdMbjbjI aj GdJejjR GdhXjaj(B- (3GdEdJRGe HGdeHGOF GdCNdGbjI hGdegfjI GdhXjajI(B- (3GdHYO GdeMhQj aj JMbjb GdJejR GdhXjaj(B- (3BdjGJ GdEYOGO hGdJCgjd GdhXjaj GdYGe ddYGedjf GdLOO(B- (3JhWjO hJaYjd GdYdGbGJ eY LejY GdCWQGa PGJ GdYdGbI HGdehXa(B- (3JfejI GdKbGaI GdEOGQjI dOi GdLgGR GdEOGQj hGdJfajPj HBdjGJ JWHjb CSdhH GdEOGQI HGdMH(B- (3eONd dJhWjO hJaYjd GdYdGbGJ GdELJeGYjI eY LejY GdCWQGa PGJ GdYdGbI HGdeDSSI(B- (3BdjGJ GdEfVHGW GdhXjaj ZjQ GdQSej ef NdGd GdEOGQI HGdJRGe GdVejQ(B- (3JfejI GdbOQI Ydi GdJacjQ GdCHJcGQj CMO BdjGJ GdJejR GdhXjaj ddYGedjf GdLOO hGdbOGei(B.s
(3GdeQGLY U(B.361s
Keywords: (3EOGQI GdCaQGOs; (3GdKbGaI GdYeGdjIs; (3GdQVG GdhXjajs; (3GdYed hGdYeGds; (3Gdbhi GdYGedIs